1982
DOI: 10.1136/bmj.285.6355.1629
|View full text |Cite
|
Sign up to set email alerts
|

Alternative medicine: cost and subjective benefit in rheumatoid arthritis.

Abstract: Seventy-eight patients with seropositive rheumatoid arthritis were asked about money spent in an attempt to help their arthritis. This included expenditure on alternative medicine, aids for the home, and conventional medicine. Most money was spent on, and most benefit was derived from, aids for the home. Sixty per cent of the patients had tried alternative medicine, but expenditure on this was relatively low and only a small proportion found it helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…It is difficult therefore to compare our findings with those from previous surveys in the UK, many of which either targeted patients attending hospital clinics and who had known diagnoses e.g. rheumatoid arthritis [14,16,17,35,36], fibromyalgia [15,37], multiple sclerosis [38] or post-spinal cord injury [39] or targeted individuals in the community [10,11] suffering from chronic pain in general and not specifically musculoskeletal pain. Surveys that looked at CAM use in primary care in the UK mainly explored access to CAM and GPs' use and attitude towards it.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is difficult therefore to compare our findings with those from previous surveys in the UK, many of which either targeted patients attending hospital clinics and who had known diagnoses e.g. rheumatoid arthritis [14,16,17,35,36], fibromyalgia [15,37], multiple sclerosis [38] or post-spinal cord injury [39] or targeted individuals in the community [10,11] suffering from chronic pain in general and not specifically musculoskeletal pain. Surveys that looked at CAM use in primary care in the UK mainly explored access to CAM and GPs' use and attitude towards it.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their great diversity, the only way to identify these treatments as a distinct group seems to have been by 'negatively' defining them as treatments that are not taught in medical schools or provided in hospitals. In 1982, this group of treatments was defined as "treatments that a conventional unit is unlikely to prescribe" [14]. Within that were included aids for the home (used by patients with arthritis) as well as herbs and acupuncture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, one survey found that CM's high cost was a prominent reason for not using it [20]. Pullar et al [9], on the contrary, found costs to be relatively low.…”
Section: Patients' Use Of CMmentioning
confidence: 96%
“…Fourteen surveys of rheumatological patients' use of CM were identified [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Collectively they point to a high prevalence of CM use among this patient group, particularly in North America (Table 1).…”
Section: Patients' Use Of CMmentioning
confidence: 99%